Emotional intelligence at the workplace: Why is it crucial for employees? - Mahbub, Antara; Barhate, Bhagyashree (International Journal of Business, Economics and Management, 2025)
In the human capital development process, employees’ behavioral issues have been discussed with high priority because of the urge to adjust to the job environment and adapt to the change management process. Emotional intelligence (EI) is the ability to understand and manage one’s own as well as other people’s emotions effectively. The qualities associated with EI, such as self-awareness, self-management, social awareness, and relationship management, are considered key factors in handling social situations and achieving success in both personal and professional life. EI has emerged as a crucial competency in today’s competitive business world to achieve organizational success. This study attempts to determine the impact of emotional intelligence in organizational workplace settings. It aims to explore how emotional intelligence positively influences employees’ job satisfaction, boosts job performance, and overall productivity through social relationships. This study adopts a literature review approach. It is descriptive in nature. Current literature on emotional intelligence has been analyzed to perceive the study’s objectives. This study finds a highly positive relationship between EI and job satisfaction. Moreover, employees with high EI show higher job performance and increased productivity. Theoretically, this study will contribute to the literature on human capital development, focusing on EI, and incorporating it into organizational frameworks. Practically, this study will contribute to human capital development practice, revealing the current demand to adopt EI in the workplace.